Incorporating social cognitive learning into learning environment of mathematical science students - Ahmad, Shamsatun Nahar; Ahmad @ Abdul Mutalib, Hawa; Thangal, Thahira Bibi TKM (Universiti Teknologi MARA, 2023)
It is essential to establish a classroom environment in which students feel safe and motivated to collaborate, cooperate, and pursue mathematical understanding. Mathematics is a core subject that all science and technology students must earn at least a grade C. This study was conducted by distributing questionnaires to 163 students enrolled in Malaysian institutions of higher education. The respondents were Mathematical Science students aged 18 to 32 with study levels ranging from diploma to master. The questionnaires include thirty questions organised into four sections: learner-centered, community centered, assessment-centered, and knowledge-centered. The purpose of this study is to investigate how the three components of social cognitive learning (SCL) influence the learning environment for mathematical science students by utilising correlation and regression analysis to determine the relationship between the variables. Incorporating the principles of SCL into the learning environment had a positive effect on student and educator engagement, as demonstrated by the findings.